Rwanda : Staff Report for the 2002 Article IV Consultation and Requests for a New Poverty Reduction and Growth Facility Arrangement and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper examines Rwanda's 2002 Article IV Consultation and Requests for a New Poverty Reduction and Growth Facility (PRGF) Arrangement and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). Rwanda's performance under the 2001 program under the PRGF was broadly satisfactory. Quantitative performance criteria for end-December 2001 were substantially met. Despite slippages in the structural reform schedule, achievements in structural performance were substantial. The authorities have finalized a poverty reduction strategy paper. The program for 2002-03 supports the poverty reduction strategy formulated in that document.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet